Technical investment analysis of the stock market - Tatro, Quint (FT Press, 2011)
"Technical analysis is often misunderstood and rarely appreciated as an art form. Through this new video series, author Quint Tatro, portfolio manager of the Tatro Capital Tactical Appreciation Fund (TCTNX) and author of Trade the Trader, takes you into the world of technical analysis through an educational process by reviewing the current market environment with actionable opportunities."--Resource description page.